Distinguer les habitus et les vertus, pour une meilleure compréhension de la formation intégrale - Cochin, Céline (Alpha Omega, 2015)
Summary: The article draws attention to the importance of a concept, which has been cast aside (either for ideological reasons or because of the evolution of modern languages): habitus. Many contemporary philosophies and currents of thought propose a return to the virtues and, in the moral, psychological and pedagogical domains, bring out the importance of a formation which is integral. It would appear that the concept of habitus, properly understood, is capable of enriching this common research. The notion of habitus presents, first of all, the difficulty of vocabulary. For example, why has this term disappeared from the French and Italian languages? How did it evolve? Pierre Bourdieu seems to have brought this term back into fashion, but he has done so by attributing to it a meaning which is almost totally opposed to that which it has enjoyed classically, it coming to mean ‘cultural unconscious’. Rediscovering habitus, without any prejudice, in the thought of Thomas Aquinas allows us to understand this notion and to deepen our grasp of its unperceived riches. Habits and virtues are two concepts, closely linked to each other, but focusing attention too hastily upon virtue means that we are not able to catch a glimpse of the much broader role which the habitus can play in the process of an integral formation. The article, which takes up the analyses and the conclusions of a thesis, entitled Avant les vertus, limits itself to questions pertaining to the distinction between habitus and virtue. Does this distinction find a raison d’être in the thought of Thomas Aquinas?, and, what would be the implications of this for the integral formation of the person? Key words: habitus, virtue, Thomas Aquinas, integral formation, virtue ethics, cultural unconscious, habit. Sommario: L’articolo pone l’accento sull’importanza di un concetto che è stato messo da parte (o per ragioni ideologiche o per l’evoluzione delle lingue moderne): habitus. Molti, tra i filosofi e scuole di pensiero contemporanee, propongono un ritorno alle virtù; e nell’ambito morale, psicologico e pedagogico rilevano l’importanza della formazione integrale. Sembra che il concetto di habitus, ben inteso, sia in grado di arricchire questa ricerca comune. La nozione di habitus presenta in primo luogo una difficoltà di vocabolario. Perché è scomparso questo termine dalla lingua francese o italiana, per esempio? Quale n’è stata l’evoluzione? Pierre Bourdieu sembra aver riposto di moda questo termine, ma dandogli un significato quasi totalmente opposto al suo senso classico, venendo a significare “inconscio culturale”. Una riscoperta senza pregiudizi dell’habitus nel pensiero di Tommaso d’Aquino permette di capire questo concetto e di approfondirne le ricchezze inosservate. Abitudine e virtù sono due concetti strettamente collegati; ma l’attenzione frettolosamente incentrata sulla virtù non lascia intravedere il ruolo più ampio che l’habitus può giocare nella formazione integrale. L’articolo, che riprende le analisi e le conclusioni della tesi dal titolo Avant les vertus, si focalizza sulla distinzione tra habitus e virtù. Questa distinzione ha una ragione d’essere nel pensiero di Tommaso d’Aquino? e quali sarebbero le implicazioni per la formazione integrale della persona? Parole chiave: habitus, virtù, Tommaso d’Aquino, formazione integrale, etica della virtù, inconscio culturale, abitudine.